Gaoping, China. Die Konstruktion der Mittleren Buddha-Halle des Chongming-Klosters im Kreis Gaoping, Provinz Shanxi. Die Arbeiten der Jahre 2018 bis 2020 - Zhao, Shipan; Schulz-Brize, Thekla; Mechelke, Klaus; Chen, Xiaocheng; Wertmann, Patrick; Wagner, Mayke (e-Forschungsberichte des DAI, 2020)
The Middle Buddha Hall of Chongming Monastery in Gaoping County, Shanxi Province is an existing wooden construction from the early period of the Northern Song Dynasty, and predates the treatise on architecture Yingzao Fashi. Its unusual main components of the dougong and the roof construction are a continuation of the style from the Tang Dynasty, which provides valuable examples for the study of the development of wooden structure in China. In the summer of 2018, a German-Chinese survey and research team measured the dougong in the northeast of the Middle Buddha Hall in detail by using 3D scanning and the technique of Structure from Motion. The surveying work and the documentation helped to further study the dougong and the roof construction of the Hall.